Availability of Zika Virus Testing Information on Local Health Department Websites in the State of Texas [14O]. (May 2017) - Adesomo, Adebayo; Page-Ramsey, Sarah M.; Ireland, Kayla; Sullivan, Adriana; Rodriguez, Emma; Ramsey, Patrick S.
Abstract : INTRODUCTION: Zika virus infection is an emerging health threat. It is important that obstetric providers can easily access Zika virus testing information. Our objective was to evaluate the availability of information about Zika virus testing on county and regional health department websites in Texas. METHODS: We reviewed all Texas county, regional, and metropolitan health department websites for information on testing patients with suspected Zika virus infection. Information abstracted included education on appropriate patient selection for testing, where to have blood drawn, where to submit specimens, availability of testing forms, and contacts for additional testing information. In cases where information about Zika virus testing did not appear immediately on the main webpage, an internal search of the site using the terms "Zika" was performed. RESULTS: Information for providers about Zika virus testing was identified on 3.1% of 254 county health department websites, 9.1% of the 11 public health region websites, and 5.0% of the 39 metropolitan health department websites. Very few websites had access to testing guidelines and testing forms available for providers. CONCLUSION: Growing concerns about Zika virus warrant guidance for healthcare providers on testing. The Centers for Disease Control recommends patients contact healthcare providers for guidance on testing, and that providers seek guidance from local public health departments. Providers in Texas have poor access to local and regional information for testing through these online resources. Improved local efforts are needed to assist providers with guidance on Zika testing.